Acoustic-Electrical Joint Localization Method of Partial Discharge in Power Transformer Considering Multi-Path Propagation Impact - Jia, Jun; Fu, Hui; Wang, Bo; Li, Yong; Yu, Yue; Cao, Yuan; Jiang, Di (Frontiers in Energy Research, 2022)
Efficient and accurate localization of partial discharge (PD) is of paramount importance to ensure the safe operation of power transformers. However, the multi-path propagation effect introduced by the reflection, refraction and diffraction of the ultrasonic signal may add significant computational complexity to the localization process and degrade the localization accuracy. This paper proposes an acoustic- electrical joint method for partial discharge location in the power transformer with the full consideration of the multi-path propagation impact. Unlike the conventional error analysis methods, a partial discharge localization model is proposed for characterizing the multipath propagation impact without the prior knowledge of the transcendental error probability. Based on the matrix inequality transformation and relaxation, the high-dimensional nonlinear localization equations are transformed into a set of second-order convex optimization equations that can be solved using the convex second-order cone program (SOCP). The proposed solution can significantly reduce the computational complexity and improve the localization accuracy as well as avoid the local optimum and slow convergence. The solution is assessed through extensive experiments based on simulations, testbed and trial deployment in comparison with the existing solutions with the localization error of about 0.1m.